High-performance concrete material adaptive to fabricated pavement and preparation method of high-performance concrete material

By adding magnesium chloride solution to the concrete and carbide curing, natural aragonite fibers are generated, which solves the problem of easy damage to prefabricated pavement panels during transportation and lifting, and achieves high toughness and strength concrete materials, meeting different working conditions requirements and reduce costs.

CN119390406APending Publication Date: 2025-02-07HOHAI UNIV +1
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411409415.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Prefabricated pavement panels are prone to cracking and damage during lifting and transportation, and existing materials are difficult to meet the dual requirements of strength and toughness, and cannot be adapted to the production of prefabricated pavement panels in places with high toughness and strength requirements.

Method used

By adding magnesium chloride solution during concrete mixing and carburizing, natural aragonite fibers are generated to enhance the toughness and strength of the concrete, high-performance concrete materials with a thickness of 6-12 cm are prepared.

Benefits of technology

It realizes the high toughness and strength of concrete materials, meets the mechanical requirements of different working conditions during transportation, lifting and service, reduces costs, and promotes the rapid development and large-scale application of prefabricated pavements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077584510000091
    Figure BDA0005077584510000091
Patent Text Reader

Abstract

The invention discloses a high-performance concrete material adapted to an assembled pavement and a preparation method thereof, and the concrete per unit volume is prepared from the following components in parts by weight: 100-220 parts of cement, 200-440 parts of fly ash, 10-30 parts of silica fume, 20-60 parts of glass beads, 10-30 parts of rubber powder, 100-200 parts of fine aggregate, 7-16 parts of a water reducing agent, 8-15 parts of a thickening agent and 0-6 parts of PVA fiber. And 1-8 parts of magnesium chloride hexahydrate, wherein the water cement ratio is 0.2-0.4. And carbonizing and curing the fiber reinforced concrete slurry to obtain the high-performance concrete material. The fiber reinforced concrete is subjected to carbonization curing to generate natural aragonite fibers, the toughness of the concrete is improved, and concrete with different aragonite contents can be prepared by adjusting the content of the magnesium chloride hexahydrate reagent, so that different toughness is achieved. According to the present invention, the fabricated pavement with characteristics of small thickness, toughness and strength meeting mechanical requirements of different working conditions during transportation, hoisting and service can be prepared, green maintenance and rapid maintenance can be achieved, and rapid development and large-scale application of the fabricated pavement can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pavement materials, and in particular to a high-performance concrete material suitable for assembled pavements. Background Art

[0002] By the end of 2023, my country's total highway mileage will have exceeded 5.75 million kilometers, with 99% of that mileage under maintenance. Many roads are experiencing rapid performance degradation and numerous road defects, marking the beginning of a maintenance era for China. Road maintenance and repair environments are complex, resulting in low efficiency. Therefore, the development of rapid road maintenance technologies is urgently needed to address my country's vast road stock. Prefabricated technology, a trending development in the civil engineering industry, offers a solution for rapid road maintenance.

[0003] Prefabricated road panels offer advantages such as a short construction period, high quality, and minimal disruption to residents, meeting current practical demands for efficient maintenance and high-quality control. However, prefabricated cement concrete road panels lack sufficient flexural strength, making them susceptible to cracking and damage during installation and transportation. Therefore, the application of prefabricated technology to road panels requires a high degree of deformation resistance. Reinforcement design can improve the flexural resistance of road panels, but this increases their weight, transportation and installation costs, and construction difficulty. Furthermore, different operating conditions require different performance requirements for prefabricated road panels, such as high strength under heavy loads. However, current prefabricated road panels fail to meet both strength and toughness requirements.

[0004] In view of this, there is an urgent need to propose a high-performance cement-based material with high toughness, small thickness and meeting the mechanical requirements of different working conditions during transportation, lifting and service for use in prefabricated road panels, so as to achieve rapid and green maintenance of the road surface, thereby promoting the rapid development and large-scale application of prefabricated pavements.

[0005] The patent "A Flexible Concrete Material Suitable for Prefabricated Pavements, Its Preparation Method, and Application CN116854424A" discloses the composition of a flexible concrete material suitable for prefabricated pavements. The flexible concrete material is prepared by adding modified cement, fly ash, a water reducer, an air entraining agent, coarse aggregate, fine aggregate, and a modified rubber-fiber dispersion. The resulting flexible concrete prefabricated pavement slabs meet the requirements for transportation, lifting, and on-site assembly, and possess the properties of both asphalt concrete and cement concrete. This effectively addresses the issues of rutting on roads with complex traffic volumes and the coordination of allowable deformation between prefabricated pavements and supporting foundations. However, the material utilizes large amounts of epoxy resin, sodium hydroxide solution, sodium starch phosphate solution, EVA emulsion, and synthetic fibers, significantly increasing costs. The resulting concrete exhibits a certain degree of toughness, but the toughness is not high, and the strength is low, making it unsuitable for the production of prefabricated pavement slabs in areas where high toughness and strength are required. Summary of the Invention

[0006] In order to overcome the above-mentioned defects, the present invention provides a high-performance concrete material suitable for prefabricated pavements and a preparation method thereof. By adding magnesium chloride solution during the concrete mixing process and undergoing carbonization curing, natural aragonite fiber is generated to enhance the toughness and strength of the concrete. A 6-12 cm thick concrete material is prepared, and the toughness and strength meet the mechanical requirements of different working conditions during transportation, lifting and service. Green and rapid curing can be achieved, promoting the rapid development and large-scale application of prefabricated pavements.

[0007] The technical solution adopted in the present invention is:

[0008] A high-performance concrete material suitable for prefabricated pavements is prepared from the following components, measured by weight per unit volume of concrete: 100-220 parts of cement, 200-440 parts of fly ash, 10-30 parts of silica fume, 20-60 parts of glass microbeads, 10-30 parts of rubber powder, 100-200 parts of fine aggregate, 7-16 parts of water reducer, 8-15 parts of thickener, 0-6 parts of PVA fiber, 1-8 parts of magnesium chloride hexahydrate, and a water-cement ratio of 0.2-0.4.

[0009] Cement, fly ash, silica fume, glass beads, and rubber powder are mixed evenly, and fine aggregate is added and stirred evenly to obtain a dry mix; then a water reducer, a thickener, and magnesium chloride hexahydrate are added to water and stirred evenly, and then added to the dry mix and stirred evenly to obtain a concrete base material; fiber is slowly added to the concrete base material, and stirred thoroughly to obtain a fiber-reinforced concrete slurry, and the fiber-reinforced concrete slurry is carbonized and cured to obtain a high-performance concrete material.

[0010] Fiber is slowly added to the concrete base material and stirred thoroughly to obtain fiber-reinforced concrete slurry; preferably, the cement is at least one of Portland cement and sulphoaluminate cement, and the strength is greater than or equal to 42.5 MPa.

[0011] Preferably, the calcium oxide content of the fly ash is less than 10%, and the silicon dioxide content of the silica ash is not less than 85%.

[0012] Preferably, the glass microspheres have a particle size of 10 to 180 μm and a wall thickness of 1 to 2 μm.

[0013] Preferably, the particle size of the rubber powder is between 0.2 and 0.9 mm.

[0014] Preferably, the fine aggregate is at least one of quartz sand, machine-made sand, and river sand, with an average particle size of 150 μm, a maximum particle size of 0.5 mm, and a fineness of 1.8 to 2.2.

[0015] Preferably, the water reducer is a polycarboxylic acid-based high-efficiency water reducer with a water reduction rate greater than 20%.

[0016] Preferably, the thickener is hydroxypropyl cellulose (CMC) thickener with a viscosity between 3500 and 4000 cpa·s.

[0017] Preferably, the fiber is a PVA fiber with a fiber diameter of 10-50 μm, a length of 6-18 mm, an elongation at break of 4-8%, an elastic modulus of about 35-45 GPa, and a breaking strength greater than 1600 MPa.

[0018] Preferably, the PVA fiber has a diameter of 39 μm, a length of 12 mm, an elongation at break of about 6%, an elastic modulus of about 40 GPa, and a breaking strength greater than 1600 MPa.

[0019] The concrete material of the invention has an initial crack strength of 2-6 MPa, an ultimate tensile strength of 4.5-12 MPa, and an ultimate tensile strain of 2%-8%.

[0020] Further preferably, a high-performance concrete material suitable for prefabricated pavement is made of the following components, in parts by weight, per unit volume of concrete: 100 parts of cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, 115 parts of fine aggregate, 7.6 parts of water reducer, 10.8 parts of thickener, 3 parts of PVA fiber, 8 parts of magnesium chloride hexahydrate, and a water-cement ratio of 0.36.

[0021] Further preferably, a high-performance concrete material suitable for prefabricated pavement comprises 100 parts cement, 200 parts fly ash, 10 parts silica fume, 20 parts glass beads, 10 parts rubber powder, 115 parts fine aggregate, 7.6 parts polycarboxylate superplasticizer, 10.8 parts sodium hydroxypropyl cellulose thickener, 3 parts PVA fiber, 1-8 parts magnesium chloride hexahydrate, and a water-cement ratio of 0.36. Carbonation curing is performed at a carbon dioxide pressure of 0.1-0.2 MPa, and curing is terminated after 48-72 hours.

[0022] By adjusting the content of magnesium chloride hexahydrate reagent, concrete with different aragonite contents can be prepared, thereby achieving different toughness.

[0023] After adjusting the carbonization pressure and carbonization time, the tensile strength and tensile strain were improved.

[0024] A method for preparing the high performance concrete comprises the following steps:

[0025] 1) Mix cement, fly ash, silica fume, glass beads and rubber powder evenly, add fine aggregate and stir evenly to obtain a dry mix;

[0026] 2) Add the water reducer and thickener into water and mix well, then add them into the dry mix and mix evenly to obtain the concrete base material;

[0027] 3) Add fibers to the concrete base and stir thoroughly for 5-15 minutes to obtain fiber-reinforced concrete slurry. Adjust the amount of water-reducing agent until the fibers are evenly dispersed and there is no bleeding, thereby obtaining fiber-reinforced concrete slurry.

[0028] 4) Pour the fiber-reinforced concrete slurry into a mold, cover with plastic wrap, and cure in the mold for 24 hours. Then, demold the mold and place it in a dry environment with a humidity of 40-60% and a temperature of room temperature for 16-20 hours. Then, place it in a high-temperature and high-pressure reactor for carbonization curing. Industrial exhaust gas with a carbon dioxide concentration of 10-30% is introduced. The temperature in the reactor is maintained at 60-80° C. and the carbon dioxide pressure is maintained at 0.1 MPa-0.2 MPa. Curing is completed after 24-72 hours to obtain a high-performance concrete material.

[0029] Further preferably, the fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is demolded and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, it is placed in a high-temperature and high-pressure reactor for carbonization curing, and industrial exhaust gas is introduced. The carbon dioxide concentration contained in the exhaust gas is 20%. The temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is 0.1MPa-0.2MPa. The curing is completed after 48 hours to obtain a high-performance concrete material.

[0030] Beneficial effects:

[0031] 1) The present invention provides a high-performance concrete material. By subjecting fiber-reinforced concrete to carbonization curing, natural aragonite fibers are generated, thereby improving the toughness of the concrete. By adjusting the content of magnesium chloride hexahydrate reagent, concrete with different aragonite contents can be prepared, thereby achieving different toughness. At the same time, by adjusting the carbonization conditions, the degree of cement carbonization is controlled to achieve different strengths. Therefore, the present invention can prepare a small thickness, and the toughness and strength meet the mechanical requirements of different working conditions during transportation, lifting and service, achieving green and rapid curing, and promoting the rapid development and large-scale application of prefabricated pavements.

[0032] 2) The high-performance concrete material provided by the present invention reduces the amount of artificial fibers added and reduces the cost.

[0033] 3) The high-performance concrete material provided by this invention incorporates silica fume and rubber powder in an appropriate mass ratio. The silica fume, with its fineness lower than that of cement and fly ash, can fill the gaps between cementitious material particles, thereby increasing the strength of the cement. The addition of rubber powder can increase defects, leading to multi-joint, stable cracking in the structure and improving the toughness of the cement.

[0034] 4) The high-performance concrete material provided by this invention uses a blend of river sand, machine-made sand, and quartz sand as fine aggregate. Compared to quartz sand, machine-made sand and river sand have a rougher surface, which increases the strength of the matrix, thereby improving overall tensile strength and tensile strain.

[0035] 5) Using low-cost materials such as fly ash, silica fume, glass beads, waste rubber powder, etc. to prepare concrete can greatly reduce costs. DETAILED DESCRIPTION

[0036] Each unit volume of concrete is made of the following components: 100-220 parts of cement, 200-440 parts of fly ash, 10-30 parts of silica fume, 20-60 parts of glass beads, 10-30 parts of rubber powder, 100-200 parts of fine aggregate, 7-16 parts of water reducer, 8-15 parts of thickener, 0-6 parts of PVA fiber, 1-8 parts of magnesium chloride hexahydrate, and a water-cement ratio of 0.2-0.4.

[0037] The cement is at least one of silicate cement and sulphoaluminate cement, and has a strength greater than or equal to 42.5 MPa.

[0038] The calcium oxide content of the fly ash is less than 10%, and the silicon dioxide content of the silica ash is not less than 85%.

[0039] The glass microbeads have a particle size of 10 to 180 μm and a wall thickness of 1 to 2 μm.

[0040] The particle size of the rubber powder is between 0.2 and 0.9 mm.

[0041] The fine aggregate is at least one of quartz sand, machine-made sand, and river sand, with an average particle size of 150 μm, a maximum particle size of 0.5 mm, and a fineness of about 2.0.

[0042] The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent with a water reduction rate greater than 20%.

[0043] The thickener is hydroxypropyl cellulose (CMC) with a viscosity between 3500 and 4000 cpa·s.

[0044] The fiber is a PVA fiber with a diameter of 39 μm, a length of 12 mm, an elongation at break of about 6%, an elastic modulus of about 40 GPa, and a breaking strength greater than 1600 Mpa.

[0045] Example 1 (control group)

[0046] A method for preparing a high-performance concrete material suitable for assembled pavement comprises the following steps:

[0047] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0048] (2) Weigh 10.8 parts of polycarboxylate superplasticizer and 10.8 parts of sodium hydroxypropyl cellulose thickener, add them into 112 parts of water, stir evenly, pour into the dry mix, and stir for 2 minutes to obtain cement paste;

[0049] (3) Add 6 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0050] (4) Pour the fiber reinforced concrete slurry into the mold, cover it with plastic wrap, and cure it with the mold for 24 hours. Then demold it and put it into an 80-degree steam curing box for high-temperature steam curing for 48 hours. After the curing is completed, perform performance testing.

[0051] Example 2

[0052] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0053] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 1 part of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0054] (3) Add 6 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0055] (4) Pour the fiber reinforced concrete slurry into the mold, cover it with plastic wrap, and cure it with the mold for 24 hours. Then demold it and put it into an 80-degree steam curing box for high-temperature steam curing for 48 hours. After the curing is completed, perform performance testing.

[0056] Example 3

[0057] A method for preparing a high-performance concrete material suitable for assembled pavement comprises the following steps:

[0058] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0059] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 1 part of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0060] (3) Add 6 parts of PVA fiber to the cement paste and stir for 10 minutes;

[0061] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial tail gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is 0.1 MPa. After 48 hours, the curing is completed to obtain a high-performance concrete material.

[0062] Example 4

[0063] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0064] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 4 parts of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0065] (3) Add 6 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0066] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial tail gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is 0.1 MPa. After 48 hours, the curing is completed to obtain a high-performance concrete material.

[0067] Example 5

[0068] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0069] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 8 parts of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0070] (3) Add 6 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0071] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial tail gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is 0.1 MPa. After 48 hours, the curing is completed to obtain a high-performance concrete material.

[0072] Example 6

[0073] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0074] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 8 parts of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0075] (3) Add 3 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0076] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial tail gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is 0.1 MPa. After 48 hours, the curing is completed to obtain a high-performance concrete material.

[0077] Example 7

[0078] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0079] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 8 parts of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0080] (3) Add 3 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0081] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial tail gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is maintained at 0.2 MPa. After 48 hours, the curing is completed to obtain a high-performance concrete material.

[0082] Example 8

[0083] (1) Weigh 100 parts of PO 42.5 cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, and 115 parts of quartz sand and mix them evenly in a mixing pot to obtain a dry mix;

[0084] (2) Weigh 10.8 parts of polycarboxylate superplasticizer, 10.8 parts of sodium hydroxypropylcellulose thickener, and 8 parts of magnesium chloride hexahydrate, add them to 112 parts of water, stir evenly, pour them into the dry mix, and stir for 2 minutes to obtain cement paste;

[0085] (3) Add 3 parts of PVA fiber to the cement paste and stir for 10 minutes.

[0086] (4) The fiber-reinforced concrete slurry is poured into a mold, covered with plastic wrap, and cured in the mold for 24 hours. After that, the mold is removed and placed in a dry environment with a humidity of 50% and a temperature of room temperature for 18 hours. Then, the mold is placed in a high-temperature and high-pressure reactor for carbonization curing. Industrial exhaust gas with a purity of 20% carbon dioxide is introduced, and the temperature in the reactor is maintained at 80°C and the carbon dioxide pressure is maintained at 0.2 MPa. The curing is completed after 72 hours to obtain a high-performance concrete material.

[0087] The concrete materials prepared in Examples 1 to 8 were tested for their working performance, mechanical properties, and cost. The results are shown in Table 1.

[0088] The ultimate tensile strain of the concrete of Examples 1-8 is between 2.36.8%, and the ultimate tensile strength is between 4.5-12.8 MPa. By adjusting the dosage of magnesium chloride hexahydrate and the carbonation curing conditions, the strength and toughness are adjustable and controllable. As can be seen from Table 1, the ultimate tensile strength and ultimate tensile strain of the control group (Example 1) are not high. When magnesium chloride hexahydrate is added and carbonation curing is not performed (Example 2), the ultimate tensile strength and ultimate tensile strain do not change significantly. When magnesium chloride hexahydrate is added and carbonation curing is performed, the ultimate tensile strength and ultimate tensile strain increase with the increase in the dosage of magnesium chloride hexahydrate (Examples 3-5). This is mainly because during the carbonation curing process, carbon dioxide reacts with cement to generate fibrous aragonite under the action of magnesium ions. Due to the high temperature curing, the aragonite can exist stably. When the PVA fiber content was reduced by half (Example 6), the tensile strength and tensile strain of the concrete decreased. However, increasing the carbonization pressure (Example 7) and carbonization time (Example 8) resulted in corresponding increases in tensile strength and tensile strain. Compared to Example 1, Example 8 achieved increases in tensile strength and tensile strain of 215% and 213%, respectively, while reducing the cost by 24%.

[0089] Table 1 Mechanical and cost test results of fiber reinforced concrete in Examples 1-8

[0090]

Claims

1. A high performance concrete material suitable for assembled pavement, characterized in that: Calculated by weight, each unit volume of concrete is made of the following components: 100-220 parts of cement, 200-440 parts of fly ash, 10-30 parts of silica fume, 20-60 parts of glass beads, 10-30 parts of rubber powder, 100-200 parts of fine aggregate, 7-16 parts of water reducer, 8-15 parts of thickener, 0-6 parts of PVA fiber, 1-8 parts of magnesium chloride hexahydrate, and the water-cement ratio is 0.2-0.

4.

2. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The cement is at least one of silicate cement and sulphoaluminate cement, and has a strength greater than or equal to 42.5 MPa.

3. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The particle size of the glass microbeads is between 10 and 180 μm, and the wall thickness is 1 to 2 μm; the particle size of the rubber powder is between 0.2 and 0.9 mm.

4. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The fine aggregate is at least one of quartz sand, machine-made sand and river sand, with an average particle size of 150 μm, a maximum particle size of 0.5 mm and a fineness of 1.8 to 2.

2.

5. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid series high-efficiency water reducing agent, and the water reducing rate is greater than 20%; the thickener is a hydroxypropyl cellulose thickener, and the viscosity is between 3500 and 4000 cpa·s.

6. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The magnesium chloride hexahydrate is of industrial grade with a purity of more than 90%.

7. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: The fiber diameter is 10-50 μm, the length is 6-18 mm, the elongation at break is 4-8%, the elastic modulus is about 35-45 GPa, and the breaking strength is greater than 1600 MPa.

8. The high performance concrete material suitable for assembled pavement according to claim 1, characterized in that: In parts by weight, per unit volume of concrete, it is made of the following components: 100 parts of cement, 200 parts of fly ash, 10 parts of silica fume, 20 parts of glass beads, 10 parts of rubber powder, 115 parts of fine aggregate, 10.8 parts of water reducer, 10.8 parts of thickener, 3 parts of PVA fiber, 8 parts of magnesium chloride hexahydrate, and the water-cement ratio is 0.

36.

9. The method for preparing the high performance concrete material suitable for assembled pavement according to any one of claims 1 to 8, characterized in that: The steps include: 1) Mix cement, fly ash, silica fume, glass beads and rubber powder evenly, add fine aggregate and stir evenly to obtain a dry mix; 2) adding a water reducer, a thickener and magnesium chloride hexahydrate into water and stirring evenly, and then adding the water reducer into the dry mix and stirring evenly to obtain a concrete base material; 3) slowly adding fibers into the concrete base material and stirring thoroughly to obtain a fiber-reinforced concrete slurry; 4) Pour the fiber reinforced concrete slurry into the mold, cover it with plastic wrap, demold it after mold curing, put it in a dry environment with a humidity of 40-60% and a temperature of room temperature for 16-20 hours, and then perform carbonization curing, keep the temperature in the reactor at 60-80° C. and the carbon dioxide pressure at 0.1 MPa-0.2 MPa, and end the curing after 24-72 hours to obtain a high-performance concrete material.

10. The method for preparing a high-performance concrete material suitable for assembled pavement according to claim 9, characterized in that: In step 4), the temperature in the reactor is maintained at 80° C. and the carbon dioxide pressure is maintained at 0.1 MPa-0.2 MPa. The curing is completed after 48 hours to obtain a high-performance concrete material.

Citation Information

Cited By

  • Low-shrinkage high-toughness concrete material as well as preparation method and application thereof

    CN120058299A

  • A high-toughness concrete material with low shrinkage, its preparation method and application

    CN120058299B

  • Concrete doped with solid waste fibers and preparation method thereof

    CN120058317A

  • A kind of concrete doped with solid waste fibers and its preparation method

    CN120058317B